The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.jmr.2005.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin relaxation of copper(II) complexes in glassy solution between 10 and 120K

Abstract: The temperature dependence, between 10 and 120 K, of electron spin-lattice relaxation at X-band was analyzed for a series of eight pyrrolate-imine complexes and for ten other copper(II) complexes with varying ligands and geometry including copper-containing prion octarepeat domain and S100 type proteins. The geometry of the CuN 4 coordination sphere for pyrrolateimine complexes with R = H, methyl, n-butyl, diphenylmethyl, benzyl, 2-adamantyl, 1-adamantyl, and tert-butyl has been shown to range from planar to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 52 publications
6
40
0
Order By: Relevance
“…The fact that such a wide range of essential temperature independence of T M is found for 1Cu 0.001% is owing to the fact that T 1 is extremely long at low temperatures. T 1 decreases slowly with increasing temperature and only reaches values comparable to T M (10 ms) above 100 K. We attribute the long T 1 to a relatively rigid lattice, as well as the square planar coordination geometry, which is predicted to give rise to longer T 1 times than a tetrahedral geometry 39 . This then suggests that a design criterion for high-temperature molecular qubits is the engineering of a long T 1 .…”
Section: Resultsmentioning
confidence: 72%
“…The fact that such a wide range of essential temperature independence of T M is found for 1Cu 0.001% is owing to the fact that T 1 is extremely long at low temperatures. T 1 decreases slowly with increasing temperature and only reaches values comparable to T M (10 ms) above 100 K. We attribute the long T 1 to a relatively rigid lattice, as well as the square planar coordination geometry, which is predicted to give rise to longer T 1 times than a tetrahedral geometry 39 . This then suggests that a design criterion for high-temperature molecular qubits is the engineering of a long T 1 .…”
Section: Resultsmentioning
confidence: 72%
“…Early fundamental work on electron spin lattice relaxation was based on ions in a crystalline lattice, as summarized in references [4–6]. Subsequent studies have found that the characteristic temperature dependence predicted for these solid state mechanisms also is observed in glassy solvents [7–9] for triarylmethyl [10, 11], nitroxyl [1214], and galvinoxyl [12] radicals, and for Cu(II) [15] and V(IV) complexes [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Early fundamental work on electron spin lattice relaxation mechanisms focused on ions in a crystalline lattice, as summarized in references [5–7]. Subsequent studies have found that the characteristic temperature dependence predicted for these solid state mechanisms, including the direct, Raman, and local-mode processes, also is observed in glasses [8–10] for triarylmethyl [11, 12], nitroxyl [1315], galvinoxyl [13] and semiquinone [16] radicals, and for Cu(II) [17] and V(IV) complexes [18]. Above the glass transition temperature, relaxation may be enhanced by tumbling-dependent modulation of g- and A-anisotropy [1923] and/or by spin rotation [24].…”
Section: Introductionmentioning
confidence: 99%